The mysteries of the great city : the politics of urban design, 1877-1937 - Fairfield, John D., 1955- (Urban life and urban landscape series., 1993)
The Mysteries of the Great City examines the physical, cultural, and political transformations of the American city between the Gilded Age and the New Deal. Focusing on New York, Chicago, and Cincinnati, John Fairfield demonstrates that these transformations before and after the advent of city planning were the result of political decisions influenced by corporate and private wealth. The expansion and reorganization of the great city stood out as the most visible symbol of the transformation. The new metropolitan form, with its skyscraping business center, industrial satellites, crowded working-class neighborhoods, and exclusive suburbs, embodied an emerging corporate order. But the metropolis also disguised the new order and gave it an apparent physical implacability and inevitability that obscured the role of choice in its creation and therefore placed it beyond criticism. Fairfield unravels the mysteries of the new form to reveal the centrality of power and politics in urban design. While acknowledging that a great many factors shaped urban development, Fairfield underscores the decisive role of human design. He argues that American cities, both before and after the advent of professional planning, have always been in some measure "planned." Discussing such figures as Frederick Law Olmsted, Henry George, Daniel Burnham, Frederic Howe, Edward Bassett, Robert E. Park, and Louis Wirth, Fairfield illuminates the political and intellectual conflicts among advocates of alternative paths of urban development. The Mysteries of the Great City will enlighten all readers interested in the development of cities, particularly urban historians and planners. In pointing to the Gilded Age as a period of great possibilities of progressive reform, this study will also reward readers interested in the historical foundations of our modern society.